Characterization of the gibberellic oxidase gene SdGA20ox1 in Sophora davidii (Franch.) skeels and interaction protein screening - Zhao, Lili; Xie, Wenhui; Huang, Lei; Long, Sisi; Wang, Puchang (Frontiers in Plant Science, 2024)
Gibberellin 20-oxidases (GA20oxs) are multifunctional enzymes involved in regulating gibberellin (GA) biosynthesis and controlling plant growth. We identified and characterized the GA20ox1 gene in a plant height mutant of Sophora davidii, referred to as SdGA20ox1. This gene was expressed in root, stem, and leaf tissues of the adult S. davidii plant height mutant, with the highest expression observed in the stem. The expression of SdGA20ox1 was regulated by various exogenous hormones. Overexpression of SdGA20ox1 in Arabidopsis resulted in significant elongation of hypocotyl and root length in seedlings, earlier flowering, smaller leaves, reduced leaf chlorophyll content, lighter leaf color, a significant increase in adult plant height, and other phenotypes. Additionally, transgenic plants exhibited a substantial increase in biologically active endogenous GAs (GA1, GA3, and GA4) content, indicating that overexpression of SdGA20ox1 accelerates plant growth and development. Using a yeast two-hybrid (Y2H) screen, we identified two SdGA20ox1-interacting proteins: the ethylene receptor EIN4 (11430582) and the rbcS (11416005) protein. These interactions suggest a potential regulatory mechanism for S. davidii growth. Our findings provide new insights into the role of SdGA20ox1 and its interacting proteins in regulating the growth and development of S. davidii.